A comparative study of land efficiency of electronics firms located within and outside development zones in Shanghai. (August 2016) - Huang, Zhiji; He, Canfei; Wei, Y.H. Dennis
Abstract: The establishment of development zones is a vital strategy for attracting foreign direct investments and developing high-tech industries in China. Due to the absence of firm-level land use data, it is unclear whether firms located within development zones consume land more efficiently than their counterparts outside development zones. To fill this gap, this study compares land use efficiency of electronics firms located within and outside development zones in Shanghai. Results indicate that electronics firms within the development zones are significantly more efficient in land uses compared to those outside development zones. This study further shows that the nature of development zones and firms' attributes both condition land use efficiency of firms. This study highlights that the higher land efficiencies of firms in development zones are linked to governmental supports, technological externalities and international linkages. Highlights: This study compares land use efficiency of electronics firms located within and outside development zones in Shanghai. Results indicate electronics firms within development zones are more efficient in land uses compared to those outside. This study shows that the nature of development zones and firms' attributes condition land use efficiency of firms. This study highlights advantages from governmental supports, technological externalities and international linkages.